1991
DOI: 10.1128/jb.173.1.276-282.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of signal sequence alterations on export of levansucrase in Bacillus subtilis

Abstract: A series of alterations in the Bacillus amyloliquefaciens levansucrase signal peptide were made by in vitro mutagenesis, and their effect on the secretion of levansucrase in Bacillus subtilis was studied. Some of the alterations resulted in a completely defective signal peptide. These included the removal of positively charged residues from the N-terminus and disruption of the hydrophobic core of the signal peptide either by introducing a charged residue or by deleting five or more amino acids. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…Because of the lack of specific probes against SpoIIR, the effects of the GV21-AM23 mutation on protein release were tested by fusing the first 30 aa of either the wildtype or the mutated SpoIIR to the soluble domain of levansucrase (lacking the N-terminal signal peptide) (Borchert & Nagarajan, 1991 ;Petit-Glatron et al, 1990). An antiserum specific for levansucrase (kindly supplied by M. F. Petit-Glatron) was used for the detection of the SpoIIR-levansucrase hybrid proteins in culture supernatants or membrane protein extracts.…”
Section: Release Of Spollr Is Not Necessary For Spollga Activationmentioning
confidence: 99%
“…Because of the lack of specific probes against SpoIIR, the effects of the GV21-AM23 mutation on protein release were tested by fusing the first 30 aa of either the wildtype or the mutated SpoIIR to the soluble domain of levansucrase (lacking the N-terminal signal peptide) (Borchert & Nagarajan, 1991 ;Petit-Glatron et al, 1990). An antiserum specific for levansucrase (kindly supplied by M. F. Petit-Glatron) was used for the detection of the SpoIIR-levansucrase hybrid proteins in culture supernatants or membrane protein extracts.…”
Section: Release Of Spollr Is Not Necessary For Spollga Activationmentioning
confidence: 99%
“…Mutations in the positively charged NH 2 region of the levansucrase signal peptide have shown that the secretion efficiency became slow when the 3 positive charges were reduced to 2 and the signal peptide was no longer processed when the charges were reduced to zero (Borchert and Nagarajan, 1991) and we showed the NH 2 -terminal regions of the mature domains had contrary charged residues to NH 2 -terminus of the signal peptide. These observations may implicate that the negatively charged residues in the NH 2 -terminal regions of the mature domains interacted with the positively charged N-terminus of the signal peptide.…”
Section: Discussionmentioning
confidence: 85%
“…At various times after initiation of chase, 1-ml samples were placed in 0.5 ml of ice-cold 15% trichloroacetic acid. Processing of radiolabeled cells for immunoprecipitation has been described elsewhere (4,39). Rabbit polyclonal antisera specific for MBP, OmpA, PhoA, and RBP were a generous gift from P. J. Bassford, Jr. Immunoprecipitates were resolved by SDS-PAGE (10% acrylamide-0.27% bisacrylamide gel) and visualized by fluorography of gels which had been soaked in an autoradiography enhancer (Entensify; DuPont) and dried.…”
Section: Methodsmentioning
confidence: 99%